DIGITALISASI LAYANAN INFORMASI DESA: RANCANG BANGUN WEBSITE PROFIL DESA CIKALONG - Pramudia, Galih; Susanti, Deffy (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This research aims to design and develop a village profile website for Cikalong Village using the Laravel framework as a digital platform to improve the accessibility of information for the community. The study addresses the lack of an integrated digital system in the village, which has limited information dissemination and promotion of local potential. The methodology employed is the Waterfall model, which involves sequential stages including requirement analysis, system design, implementation, testing, and maintenance. Data collection was carried out through interviews and observations with village officials to identify user needs and system requirements. The developed website provides various features such as village profile, government structure, public services, facilities, local resources, news and events, product promotion (UMKM), gallery, contact page, and an admin dashboard for content management. The system was built using Laravel for backend development, MySQL for database management, Bootstrap for responsive interface, and tested with the black-box method. The results show that the website successfully supports the dissemination of village information, enhances transparency, and serves as a medium for promoting local products. User feedback indicated positive responses regarding usability and relevance of the features